2016
DOI: 10.1253/circj.cj-16-0924
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Apoptosis and Efferocytosis in the Pathogenesis of Atherosclerosis

Abstract: Macrophage apoptosis and the ability of macrophages to clean up dead cells, a process called efferocytosis, are crucial determinants of atherosclerosis lesion progression and plaque stability. Environmental stressors initiate endoplasmic reticulum (ER) stress and activate the unfolded protein response (UPR). Unresolved ER stress with activation of the UPR initiates apoptosis. Macrophages are resistant to apoptotic stimuli, because of activity of the PI3K/Akt pathway. Macrophages express 3 Akt isoforms, Akt1, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
178
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(186 citation statements)
references
References 119 publications
(160 reference statements)
5
178
0
3
Order By: Relevance
“…The death receptor Fas and downstream signaling are known as a representative extrinsic pathway of apoptosis in macrophages . In contrast, Akt signaling, which is constitutively active in macrophages, is known to be a major anti‐apoptotic pathway in macrophages . The present study showed that Fas‐mediated signaling and the PI3K/Akt pathway play a role in the apoptosis of hepatic macrophages, and that CHI3L1 promotes the apoptosis of hepatic macrophages by decreasing Fas expression and activating Akt signaling.…”
Section: Discussionsupporting
confidence: 46%
“…The death receptor Fas and downstream signaling are known as a representative extrinsic pathway of apoptosis in macrophages . In contrast, Akt signaling, which is constitutively active in macrophages, is known to be a major anti‐apoptotic pathway in macrophages . The present study showed that Fas‐mediated signaling and the PI3K/Akt pathway play a role in the apoptosis of hepatic macrophages, and that CHI3L1 promotes the apoptosis of hepatic macrophages by decreasing Fas expression and activating Akt signaling.…”
Section: Discussionsupporting
confidence: 46%
“…As plaques progress, efferocytosis becomes defective, which promotes the formation of clinically dangerous necrotic plaques (Thorp and Tabas, 2009; Linton et al, 2016). To study the consequences of defective macrophage mitochondrial fission in this setting, Drp1 f/fl Lysmcre +/ − (Cre−/−) and Drp1 f/fl Lysmcre +/ − (Cre+/−) mice were crossed onto the Ldlr − / − background and fed a high-fat Western-type diet (WD) for 12 weeks to induce advanced atherosclerosis.…”
Section: Resultsmentioning
confidence: 99%
“…i.e. , plaque necrosis and induced inflammation, are critical in promoting plaque disruption and acute vascular thrombosis (Schrijvers et al, 2005; Thorp and Tabas, 2009; Linton et al, 2016). Impaired efferocytosis in advanced lesions almost certainly has multiple etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…A lesional macrophage resolution process that has received particular attention in the field of atherosclerosis is efferocytosis (Tabas, 2005; Schrijvers et al, 2007; Linton et al, 2016; Van Vre et al, 2012). Efferocytosis is mediated through phagocyte receptors, apoptotic cell ligands, bridging proteins, and chemoattractants.…”
Section: Resolution Of Inflammation Is Impaired In Atherosclerosis Anmentioning
confidence: 99%